Las relaciones intrafamiliares y la autoestima de los estudiantes del bachillerato del colegio técnico nacional 6 de Octubre de la ciudad de Huaquillas. Año 2013 - Ocampo Lapo, María Fernanda (2015)
This thesis work refers to family relationships and self-esteem of high school students from the National Technical College “6 de Octubre” Huaquillas- Academic Year 2013; the general objective was to analyze the influence of family relationships on self-esteem; It is a descriptive study; the methods used were scientific, analytical, synthetic, inductive, descriptive and statistical. The instruments applied were: the self –esteem test Lucy Redyl and the scale for the evaluation of Intrafamily Relations, in a sample of 150 students; 44% presents a half-esteem; in family relationships in regard to the dimension of unity and support are mostly at the medium level with 45%, in the dimension of expression similarly in the medium level with 53% and the extent of difficulties mainly they are with 40% in the medium-high level. As we conclude that the family relationships are mainly related to levels of self-esteem, hence the importance of improving family dynamics focusing in the perspective of providing useful tools such as assertive communication, this will allows maintaining suitable relationships and thus improving the quality of life of students.